Factors Affecting Employees’ Religiosity at the Public Workplace in Kepulauan Riau, Indonesia - Wayu Eko Yudiatmaja; Edison Edison; Tri Samnuzulsari (Department of Government Studies Universitas Muhammadiyah Makassar, 2018)
Currently, religiosity has become an emerging topic in the literature of public administration. Most research examines the dimensions of religiosity and their relationships with various organizational dimensions. Much less attention, however, has been paid to analyze the factors affecting employees’ religiosity, particularly in the context of public organization. Therefore, this study investigates the critical factors affecting employees’ religiosity. This study is conducted on 262 public servants in the Government of Kepulauan Riau Province. An extensive literature and questionnaire were used to identify the factors affecting employees’ religiosity. This study applied statistical methods with ranking and factor analyses to verify and analyze the factors. Ranking analysis results the most important factors, namely family religious activity. Factor analysis constructs 5 components, including personal belief system, implementing religious belief, family religiousness, religious practices, and belief on the death. Theoretical, methodological, and practical implications are provided in the light of these findings.